Deltoid muscle shape analysis with magnetic resonance imaging in patients with chronic rotator cuff tears - Meyer, Dominik C (BioMed Central, 2013)
BACKGROUND: It seems appropriate to assume, that for a full and strong global shoulder function a normally innervated and active deltoid muscle is indispensable. We set out to analyse the size and shape of the deltoid muscle on MR-arthrographies, and analyse its influence on shoulder function and its adaption (i.e. atrophy) for reduced shoulder function. METHODS: The fatty infiltration (Goutallier stages), atrophy (tangent sign) and selective myotendinous retraction of the rotator cuff, as well as the thickness and the area of seven anatomically defined segments of the deltoid muscle were measured on MR-arthrographies and correlated with shoulder function (i.e. active abduction). Included were 116 patients, suffering of a rotator cuff tear with shoulder mobility ranging from pseudoparalysis to free mobility. Kolmogorov-Smirnov test was used to determine the distribution of the data before either Spearman or Pearson correlation and a multiple regression was applied to reveal the correlations. RESULTS: Our developed method for measuring deltoid area and thickness showed to be reproducible with excellent interobserver correlations (r = 0.814–0.982). The analysis of influencing factors on active abduction revealed a weak influence of the amount of SSP tendon (r = −0.25; p < 0.01) and muscle retraction (r = −0.27; p < 0.01) as well as the stage of fatty muscle infiltration (GFDI: r = −0.36; p < 0.01). Unexpectedly however, we were unable to detect a relation of the deltoid muscle shape with the degree of active glenohumeral abduction. Furthermore, long-standing rotator cuff tears did not appear to influence the deltoid shape, i.e. did not lead to muscle atrophy. CONCLUSIONS: Our data support that in chronic rotator cuff tears, there seems to be no disadvantage to exhausting conservative treatment and to delay implantation of reverse total shoulder arthroplasty, as the shape of deltoid muscle seems only to be influenced by natural aging, but to be independent of reduced shoulder motion.